المجاز في القرآن بين المفسرين والبلاغيين - أحمد، صفية شوقي محمد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2022)
عني علماؤنا منذ انبثاق نور الهداية على العالم بالقرآن الكريم عناية شملت جميع نواحيه وأحاطت بكل ما يتصل به، فكان لذلك أثره الطيب في حياة البشر بصفة عامة، وحياة المسلم بصفة خاصة، ومن تلك النواحي ما يختص بعلوم البلاغة التي تبرز خصائص اللغة العربية وجمالها، وبيان مظاهر الإعجاز في القرآن، والكشف عن أسراره الأدبية، وتبحث في مفردات اللغة، والتماس شواردها وشواهدها، وضبط ألفاظها، وتحديد معانيها، وإن وقع خلاف فما أريد به إلا صيانة القرآن أن يعدو عليه تحريف أو غموض، ومن فضل الله علينا في هذا العصر أن الركب سائر لم يقف ولم يفتر، وأن حب البحث والتدقيق ما زال يسيطر على المسلمين وينتقل فيهم من جيل إلى جيل يتناولون كل المسائل المتصلة بألفاظ القرآن بالفحص والتمحيص في دراسات موسعة تهدف إلى خدمة القرآن الكريم، ومن تلك المسائل مسألة المجاز في القرآن الكريم. Since the emergence of the light of guidance on the world with the Holy Qur’an, our scholars have taken care of all its aspects and encompassed everything related to it, and this had a good impact on human life in general, and the life of a Muslim in particular, and from these aspects is the science of rhetoric that highlights the characteristics and beauty of the Arabic language, and a statement The manifestations of the miraculousness in the Qur’an, revealing its literary secrets, looking into the vocabulary of the language, seeking its references and evidence, controlling its words, and defining its meanings. Others did not stop and did not falter, and that the love of research and scrutiny still dominated Muslims and was transmitted in them from generation to generation. They deal with all issues related to the words of the Qur’an with examination and scrutiny in extensive studies aimed at serving the Holy Qur’an, and among those issues is the issue of metaphor in the Holy Qur’an.
Keywords: البلاغة العربية -- القرآن الكريم -- اللغة العربية -- المجاز العقلي